1996
DOI: 10.1136/jcp.49.10.810
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA in squamous cell carcinoma of the lung.

Abstract: Aim-To compare the incidence of squamous cell carcinoma (SCC) of the lung in Okinawa with that in Niigata on the mainland. Methods-All patients presenting with SCC ofthe lung in Okinawa and Niigata in 1993 were included in the study. Diagnoses were confirmed by conventional histological examination of paraffin wax sections. Human papillomavirus (HPV) was detected by non-isotopic in situ hybridisation (NISH) and polymerase chain reaction (PCR) amplification with primers specific for the E6 and E7 regions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
79
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 22 publications
8
79
1
1
Order By: Relevance
“…Moreover, female lung cancer cases were more prone to HPV 16 infection than males and the prevalence in adenocarcinoma was higher than that of squamous carcinomas. For this difference in tumor type, although a previous study had detected HPV in up to 79% of squamous carcinoma of the lung, 11 Miyagi et al 12 had revealed a decreasing trend in the prevalence of HPV in lung squamous carcinoma from 79% in 1993 to 24% in 1998. Furthermore, HPV DNA was detected in a high proportion (78%) of lung adenocarcinoma in a previous study.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, female lung cancer cases were more prone to HPV 16 infection than males and the prevalence in adenocarcinoma was higher than that of squamous carcinomas. For this difference in tumor type, although a previous study had detected HPV in up to 79% of squamous carcinoma of the lung, 11 Miyagi et al 12 had revealed a decreasing trend in the prevalence of HPV in lung squamous carcinoma from 79% in 1993 to 24% in 1998. Furthermore, HPV DNA was detected in a high proportion (78%) of lung adenocarcinoma in a previous study.…”
Section: Discussionmentioning
confidence: 98%
“…3), familial tumor history (4), or diet (5,6), may also be associated with the development of lung cancer (7). In Western countries, 70% to 90% of lung cancers are attributable to cigarette smoking, whereas in Taiwan, only 7% of female lung cancer cases are associated with smoking (8,9). Many genes [e.g., TP53 (10,11), EGFR (12, 13), KRAS (14), PIK3CA (15), and EML4-ALK (16)] have been reported in association with lung cancer in never smokers, although the molecular mechanisms of NSCLC in nonsmoking women still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Etiological involvement of HPV in development of lung cancer was originally postulated (8)(9)(10). Inconsistency in prevalence of human papillomavirus (HPV) infection in lung cancer was found among recent studies from different countries with racial and geographic variations.…”
Section: Introductionmentioning
confidence: 99%